2022
DOI: 10.3389/fbioe.2022.997622
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen/sulfur dual-doped micro-mesoporous hierarchical porous carbon as host for Li-S batteries

Abstract: A simple hydrothermal process employing sucrose and glutathione as the source of carbon and nitrogen-sulfur, respectively, a porous carbon/sulfur composite material doped with nitrogen and sulfur (NSPCS) was synthesized. The detailed structure information of the material was characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. The morphology information was investigated through Scanning Electron Microscope (SEM) methods. Structure of the pores and pore size d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…This means that the conductivity of elemental sulfur was significantly increased after combined with the NS-FPC carbon matrix. Surprisingly, compared with previous published articles ( Zhao et al, 2019 ; Zhao et al, 2022a ; Zhao et al, 2022b ), the electrochemical performance of NS-FPC/S composite showed a considerable improvement.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…This means that the conductivity of elemental sulfur was significantly increased after combined with the NS-FPC carbon matrix. Surprisingly, compared with previous published articles ( Zhao et al, 2019 ; Zhao et al, 2022a ; Zhao et al, 2022b ), the electrochemical performance of NS-FPC/S composite showed a considerable improvement.…”
Section: Resultscontrasting
confidence: 87%
“…From the high-resolution XPS spectra analysis of S2p ( Figure 2D ), it can be concluded that two characteristic peaks near 164.25 and 165.35 eV correspond to the C-S-C and C=S bonds, respectively. The dual-doping of N–S heteroatoms can effectively improve the conductivity of carbon materials and increase the active site, which is particularly important for enhancing the electrochemical performance of Li–S batteries ( Zhao et al, 2022b ; Yang et al, 2022 ; Qi et al, 2023 ). The XPS results show that nitrogen and sulfur atoms were both successfully doped into the carbon materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the P2p spectra ( Fig 2D ), it contains two peaks of 133.45 eV (P-C) and 134.45 eV (P-O) [ 27 ]. The dual-doping of N-P heteroatoms in NP-PSC sample can effectively improve the conductivity and increase the active site, which is particularly important for enhancing the electrochemical performance of Li-S batteries [ 28 30 ]. The XPS results of NP-PSC/S sample was also displayed in Fig 2E .…”
Section: Resultsmentioning
confidence: 99%
“…For the P2p spectra (Fig 2D ), it contains two peaks of 133.45 eV (P-C) and 134.45 eV (P-O) [27]. The dual-doping of N-P heteroatoms in NP-PSC sample can effectively improve the conductivity and increase the active site, which is particularly important for enhancing the electrochemical performance of Li-S batteries [28][29][30]. The XPS results of NP-PSC/S sample was also displayed in Fig 2E . The XPS survey of NP-PSC/S (Fig 2E) exhibits six main characteristic peaks at 533, 395, 285, 230, 165 and 135 eV, which is attributed to the O1s, N1s, C1s, S2s, S2p and P2p peaks, respectively.…”
Section: Plos Onementioning
confidence: 99%